KEJADIAN STROKE ISKEMIK PADA PASIEN POSITIF COVID-19 TERKONFIRMASI DI RUMAH SAKIT UNIVERSITAS INDONESIA - Rakhmad Hidayat; Gemia Clarisa Fathi; Ramdinal Aviesena Zairinal; Raden Rara Diah Handayani; Mohammad Kurniawan; Taufik Mesiano; Al Rasyid; Salim Harris (NEURONA, 2021)
Coronavirus disease 2019 (COVID-19) is not only disrupts the respiratory system, it can disrupt various organ systems, one of which is the central nervous system. Indonesia still has a little literature that discusses COVID-19 and its relation to ischemic stroke. This study aims to report the course of ischemic stroke cases in patients who have been confirmed positive for COVID-19. A 56 year old man presented with confirmed COVID-19, the patient had a history of type 2 diabetes mellitus and also a history of dyslipidemia. At initial presentation the patient did not complain of neurological symptoms, but after 12 days of treatment the patient complained of weakness in the left side of the upper leg. The CT scan of the head with contrast revealed an infarction in the peripheral area, perfusion CT found that the patient was hypoperfused in the right cerebral hemisphere area without the presence of a large core infarction or a clear perfusion mismatch defect. CT angiography did not reveal stenosis or occlusion of the large vessels. It can be concluded that ischemic stroke in COVID-19 patients can occur due to various underlying factors, one of which is hypercoagulability. Keywords: COVID-19, Stroke, Universitas Indonesia Hospital